The Nonlinear Behavior of RC Medium-Rise Frame Buildings Designed According to Different Lateral Force Design Patterns - بدران عبق; فدوى عيسى; بسام حويجة (Latakia University Journal -Engineering Sciences Series, 2024)
Earthquakes are considered one of the most important dynamic loads that affect structures due to their destructive energy that cannot be avoided. However, damages and losses can be minimized through the design and construction of well-designed buildings. Achieving economical designs for earthquake-resistant buildings is a challenge that requires sufficient knowledge of the factors that affect the design. The lateral force distribution pattern (LFDP) used in the structural design phase is a very important factor in the behavior of the designed building. These distributions may lead to significant nonlinear deformations because they may not represent the actual response during exposure to severe earthquakes, causing the building to behave unexpectedly during the nonlinear phase. This research aims to study the effect of six models of lateral force distribution patterns on the nonlinear behavior of 3-D concrete frames designed according to the Syrian Arab Code. Static and dynamic nonlinear analyses were conducted using the IDARC program for the studied building models using the seismic records of El-Centro (1940), Kobe (1995), and Northridge (1994). The results showed that the distributions of the code led to good outcomes in medium-rise buildings. However, as the nonlinearity increased, some forms of lateral loads derived from the reference studies exhibited better behavior in terms of damage and the distribution of the drift ratio with height.